2010
DOI: 10.1093/gerona/glq004
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cell Count and C-Reactive Protein Are Independent Predictors of Mortality in the Oldest Old

Abstract: Background. White blood cell (WBC) count is, like C-reactive protein (CRP), a clinical marker of inflammation and predicts cardiovascular disease and mortality in middle-aged populations. Limited data exist on the association between WBC count and mortality in the oldest old. Moreover, because CRP and WBC count are closely linked, it is not known whether WBC count and CRP are independent risk factors for mortality. We assessed the independent predictive value of WBC count and CRP levels in relation to mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 32 publications
5
28
0
Order By: Relevance
“…These biomarkers have been associated with frailty and also with morbidity and mortality in older adults (Willems et al, 2010; Kim et al, 2013; Salazar et al, 2014). The association between time spent in sedentary behavior and increased CRP concentrations and leukocyte counts identified in large population studies (Healy et al, 2011; Pinto Pereira et al, 2012; León-Latre et al, 2014) has received considerable attention in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…These biomarkers have been associated with frailty and also with morbidity and mortality in older adults (Willems et al, 2010; Kim et al, 2013; Salazar et al, 2014). The association between time spent in sedentary behavior and increased CRP concentrations and leukocyte counts identified in large population studies (Healy et al, 2011; Pinto Pereira et al, 2012; León-Latre et al, 2014) has received considerable attention in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that neutrophils could produce cytokines, oxidation metabolites, and free radicals that might cause oxidative damages to various tissues (e.g., muscles) and organ systems (Wu et al 2009), and evidently, this process could lead to an increased mortality risk (Babior 1978). It could be a potential limitation for many studies that did not differentiate WBC to scrutinize the effect of different WBC subtypes (Willems et al 2010). It is particularly intriguing to examine whether the identified associations of WBC with mortality in current studies are mostly accounted for by neutrophil or not (Ruggiero et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the proposed role of inflammation in CKD progression and CVD outcomes, leukocytosis has been predictive of incident and prevalent CKD cases [4,13,14,15]. While C-reactive protein (CRP) and white blood cell count (WBC) have both been used as markers of systemic inflammation, the correlation between the two markers is low [16]. Accordingly, Sabatine et al [17] and Brown et al [18] showed that in subjects with coronary artery disease, elevated WBC even in the context of low CRP was strongly predictive of greater mortality.…”
Section: Introductionmentioning
confidence: 99%